1987
DOI: 10.1002/ajmg.1320280302
|View full text |Cite
|
Sign up to set email alerts
|

Limb body wall complex: I. Pathogenesis

Abstract: Twenty-five fetuses with limb body wall complex (LBW complex) were evaluated. The diagnosis was based on two out of three of the following: exencephaly/encephalocele with facial clefts; thoraco- and/or abdominoschisis; and limb defect. Ninety-five percent (24/25) of the fetuses had associated internal structural defects. In 72% (18/25) the internal defects have been recognized as being secondary to vascular disruption. Concordance was not found between the side and location of the body wall defect versus the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
257
1
12

Year Published

1997
1997
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 266 publications
(283 citation statements)
references
References 29 publications
13
257
1
12
Order By: Relevance
“…Van Allen et al [1987a] concluded that there was no correlation between either the cranio-caudal location or sidedness of the schisis and the internal or limb anomalies. Other authors have disagreed [e.g., Pagon et al, 1979;Russo and Vecchione, 1996;Craven et al, 1997;Luehr et al, 2002].…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Van Allen et al [1987a] concluded that there was no correlation between either the cranio-caudal location or sidedness of the schisis and the internal or limb anomalies. Other authors have disagreed [e.g., Pagon et al, 1979;Russo and Vecchione, 1996;Craven et al, 1997;Luehr et al, 2002].…”
Section: Discussionmentioning
confidence: 98%
“…Finally, Hartwig et al [1989] proposed that the same ectodermal anomaly causes a deficiency of intermediate mesoderm and thus accounts for malformations such as renal agenesis. This seems contradicted by those cases where the abnormal organ is contralateral to the body wall defect [Van Allen et al, 1987a]. Furthermore the internal organs are known to derive from the inward migration of epiblasts at the primitive streak; the progenitors of the mesoderm.…”
Section: Review Of Prior Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations